Meta Analysis: The Effect of Emotional Qoutient (EQ) on Students' Mathematics Learning Outcomes - Nur, Ahmad Hasan; Angriani, Andi Dian; Latuconsina, Nurkhalisah; Nursalam; Rasyid, Muhammad Rusydi (Department of Mathematics Education, 2023)
This research aims to determine the influence of emotional qoutient (EQ) on students' mathematics learning outcomes. The type of research used is meta-analysis which is a quantitative research method. Data collection was carried out by searching for relevant articles according to the topic being studied on internet network sites such as Google Scholar, Research gate One Search, Open Knowledge Map, Search, and Microsoft Academic with the keyword influence of emotional quotient on students' mathematics learning outcomes. The sampling technique uses purposive sampling technique. The samples analyzed are research reports that meet predetermined criteria. The instrument used is a coding sheet (coding data). Data analysis was carried out by looking for the effect size value using the summary effect formula. Based on the analysis carried out, it was found that there was an influence of emotional quotient on the mathematics learning outcomes of moderate students with an average effect size of 0.778 and was included in the category. Thus, educators or stakeholders in the world of education can design more holistic learning programs by including EQ aspects to increase the effectiveness of mathematics learning and student learning outcomes.